Towards the "Perfect" Weather Warning Bridging Disciplinary Gaps through Partnership and Communication - Golding, Brian (Springer International Publishing : Imprint: Springer, 2022)
This book is about making weather warnings more effective in saving lives, property, infrastructure and livelihoods, but the underlying theme of the book is partnership. The book represents the warning process as a pathway linking observations to weather forecasts to hazard forecasts to socio-economic impact forecasts to warning messages to the protective decision, via a set of five bridges that cross the divides between the relevant organisations and areas of expertise. Each bridge represents the communication, translation and interpretation of information as it passes from one area of expertise to another and ultimately to the decision maker, who may be a professional or a member of the public. The authors explore the partnerships upon which each bridge is built, assess the expertise and skills that each partner brings and the challenges of communication between them, and discuss the structures and methods of working that build effective partnerships. The book is ordered according to the "first mile" paradigm in which the decision maker comes first, and then the production chain through the warning and forecast to the observations is considered second. This approach emphasizes the importance of co-design and co-production throughout the warning process. The book is targeted at professionals and trainee professionals with a role in the warning chain, i.e. in weather services, emergency management agencies, disaster risk reduction agencies, risk management sections of infrastructure agencies. This is an open access book.